Design, Synthesis and in vitro Antimicrobial Activity Evaluation of Novel Hybrids of Lichexantone-THC Derivatives - Micheletti, Ana Camila; Honda, Neli Kika; Carvalho, Nadia Cristina Pereira; de Lima, Dênis Pires (Orbital: The Electronic Journal of Chemistry, 2015)
Two novel hybrid lichexantone-THC (benzopirane group) derivatives as potential antimicrobial agents were designed and prepared from norlichexanthone and (S)-cis-verbenol in two steps. The newly synthesized compounds were characterized by 1H-NMR, 13C-NMR and MS. In addition, we evaluated the in vitro antimicrobial activity against Gram-positive (Staphylococcus aureus, Enterococcus faecalis and Enterococcus faecium) and Gram- negative (Escherichia coli, Enterobacter cloacea, Klebisiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa) bacterial strains. The bioassay results indicate that the compounds namely 5 and 6 proved active against Gram-positive strains (standard and clinical) in comparison with reference drugs. DOI: http://dx.doi.org/10.17807/orbital.v7i4.788